Beyond Afghanistan: The new ISAF strategy. Implications for Central Asia - Andrea Schmitz (Stiftung Wissenschaft und Politik (SWP), 2010)
NATO's new Afghanistan Strategy, which provides for a step-by-step transfer of security responsibilities to the Kabul government starting in 2011, has been met with concern by the country's Central Asian neighbours. Indeed, the relatively stable political environment in Central Asia is largely thanks to the western presence in the Hindu Kush. With the new ISAF strategy, the responsibility for regional security will be transferred to the Central Asian partners over the medium term. These nations, however, are poorly prepared for these responsibilities and will continue to expect further assistance from the Europeans and their transatlantic allies to compensate for deficits in the region's security arrangement. The EU should steer in a different direction by reassessing regional cooperation in the context of its Central Asia strategy and by demanding more initiative from its partners
Keywords: 320